Enhancing Repurchase Intention on Digital Platforms Based on Shopping Well-Being Through Shopping Value, Trust and Impulsive Buying - Trinh Le Tan; Khanh Nguyen Chau Ngoc; Hien Le Thi Thanh; Hoai Nguyen Thi Thu; Uyen Vo Truong Hoang (SAGE Open, 2024)
The surge in digital platforms has revolutionized how consumers purchase, favoring online shopping. Despite its popularity, customer loyalty in this sphere requires enhancement. Companies are striving to augment loyalty and repurchase intention among consumers. However, the factors driving repurchase intention through shopping well-being in the online context, particularly in Vietnam, remain incompletely understood. This study examines shopping value components, including utilitarian and hedonic values, while exploring their relationships with customer trust and impulsive buying, influencing repurchase intention through customer’s shopping well-being on digital platforms. Employing a mixed-method approach, the study conducts qualitative interviews with online shoppers, marketers, and researchers to refine assessment scales for the Vietnamese context. A quantitative survey will gather data and use Covariance-based Structural Equation Modeling (CB-SEM) to test proposed hypotheses. In addition, the PRISMA model is applied in the systematic evaluation of literature reviews. This research offers a theoretical model for understanding consumer behavior in the Vietnamese online shopping landscape. Additionally, it furnishes valuable insights for digital platform sellers aiming to improve customers’ repurchase intention by refining the shopping experience and well-being.